An upstream open reading frame impedes translation of the huntingtin gene - Lee, Joseph (Oxford University Press, 2002)
Expansion of a CAG tract within the huntingtin gene, leading to the production of a protein with an expanded polyglutamine tract, is responsible for Huntington’s disease. We show here that the 5′ untranslated region (UTR) of the huntingtin gene plays an important role in controlling the synthesis of huntingtin. In particular, the 5′ UTR contains an upstream open reading frame (uORF) encoding a 21 amino acid peptide. We demonstrate that the presence of this uORF negatively influences expression from the huntingtin mRNA. Our results suggest a role for the uORF in limiting ribosomal access to downstream initiation sites. Mechanisms involving the post-transcriptional regulation of huntingtin are not well understood, and this may be an important way of regulating huntingtin protein levels.